Strategic bidding of generating units in competitive electricity market with considering their reliability - Soleymani, S.; Ranjbar, A.M.; Shirani, A.R. (International journal of electrical power & energy systems, 2008)
In the restructured power systems, they are typically scheduled based on the offers and bids to buy and sell energy and ancillary services (AS) subject to operational and security constraints. Generally, no account is taken of unit reliability when scheduling it. Therefore generating units have no incentive to improve their reliability. This paper proposes a new method to obtain the equilibrium points for reliability and price bidding strategy of units when the unit reliability is considered in the scheduling problem. The proposed methodology employs the supply function equilibrium (SFE) for modeling a unit’s bidding strategy. Units change their bidding strategies and improve their reliability until Nash equilibrium points are obtained. GAMS (general algebraic modeling system) language has been used to solve the market scheduling problem using DICOPT optimization software with mixed integer non-linear programming.